Sustainability Analysis of Urban Settlement Distribution in Kanigoro - Widodo, Trisno; Antariksa; Putra, Fadillah; Hariyani, Septiana; Satria, Punjung Aziz (Postgraduate School of Universitas Brawijaya, 2024)
Cities develop as activity centers because they provide more facilities than rural areas. After being established as the capital of Blitar Regency based on Government Regulation No. 3/2010 dated January 5, 2010, Kanigoro experienced a shift from rural to urban land use followed by an increase in population, causing the quality of the environment to decline, requiring the structuring of sustainable urban development from social, economic, and environmental aspects. This study examines the development pattern of urban settlements with an environmental perspective to build an understanding of the spatial growth process that occurs in urbanization and urban formation in a small suburban area. This research uses a quantitative approach from secondary data analysis. Initial identification of the urban regions using Arc GIS to analyze land use conditions, especially settlements, using secondary data images in 2022 to obtain land use and settlement area maps in 2022. Kanigoro Urban Settlement area develops following grid and linear patterns, following road access and service trade. The thick rural-urban mix is primarily agricultural and residential. The ecological approach of Kanigoro Urban tends to be differentiated; the population lives scattered in convenient areas that are easy to reach, and spatial expression is fragmented, including